Odpowiedzi

Najlepsza Odpowiedź!
2010-04-14T18:32:28+02:00
-5t+t-6-7t+8t+2+2t dla t = -3,2
-4-1t=-4-1*(-3,2)=-4+3,2=-0,8

-7x+6y+3x-2y+x-3y dla x = - 2/3 i y = 4/7
-3x+y=-3 (-2/3) + 4/7= 2+4/7=2 i 4/7
2 5 2
2010-04-14T18:33:24+02:00
-t-4=3,2-4=-0,8
y-3x=4/7+2=2 4/7
1 5 1
2010-04-14T18:35:31+02:00
-5t+t-6-7t+8t+2+2t dla t = -3,2
-4t-6+t+2+2t dla t = -3,2
-t-6+2 dla t = -3,2
-t-4 dla t = -3,2

3,2-4=-0,8
, albo
-3,2-4=-7,2



-7x+6y+3x-2y+x-3y dla x = - 2/3 i y = 4/7
-7x+3x+x+6y-2y-3y dla x = - 2/3 i y = 4/7
-3x+y dla x = - 2/3 i y = 4/7
-3*-2/3+4/7
2+4/7=2i4/7
1 5 1